Adaptations for bipedal walking: Musculoskeletal structure and three-dimensional joint mechanics of humans and bipedal chimpanzees (Pan troglodytes). Issue 168 (July 2022) - O'Neill, Matthew C.; Demes, Brigitte; Thompson, Nathan E.; Larson, Susan G.; Stern, Jack T.; Umberger, Brian R.
Abstract: Humans are unique among apes and other primates in the musculoskeletal design of their lower back, pelvis, and lower limbs. Here, we describe the three-dimensional ground reaction forces and lower/hindlimb joint mechanics of human and bipedal chimpanzees walking over a full stride and test whether: 1) the estimated limb joint work and power during the stance phase, especially the single-support period, is lower in humans than bipedal chimpanzees, 2) the limb joint work and power required for limb swing is lower in humans than in bipedal chimpanzees, and 3) the estimated total mechanical power during walking, accounting for the storage of passive elastic strain energy in humans, is lower in humans than in bipedal chimpanzees. Humans and bipedal chimpanzees were compared at matched dimensionless and dimensional velocities. Our results indicate that humans walk with significantly less work and power output in the first double-support period and the single-support period of stance, but markedly exceed chimpanzees in the second double-support period (i.e., push-off). Humans generate less work and power in limb swing, although the species difference in limb swing power was not statistically significant. We estimated that total mechanical positive 'muscle fiber' work and power were 46.9% and 35.8% lower, respectively, in humans than in bipedal chimpanzees at matched dimensionless speeds. This is due in part to mechanisms for the storage and release of elastic energy at the ankle and hip in humans. Furthermore, these results indicate distinct 'heel strike' and 'lateral balance' mechanics in humans and bipedal chimpanzees and suggest a greater dissipation of mechanical energy through soft tissue deformations in humans. Together, our results document important differences between human and bipedal chimpanzee walking mechanics over a full stride, permitting a more comprehensive understanding of the mechanics and energetics of chimpanzee bipedalism and the evolution of hominin walking.